Flow and heat transfer over a thin needle immersed in a porous medium filled with an Al2O3-water nanofluids using Buongiorno's two-phase model. Issue 1 (31st December 2022) - Nayak, M. K.; Oloniiju, S. D.; Mondal, S.; Goqo, S. P.; Sibanda, P.
Abstract : In this study, we analyze the flow and heat transfer in a two-phase non-homogeneous Buongiorno fluid model over a thin needle immersed in a porous medium filled with an A l 2 O 3 -water nanofluid. The model takes into account particle Brownian movement and thermophoresis that significantly influence the thermal conductivity and other properties of the nanofluid leading to an increase in the rate of heat transportation. The study seeks to investigate the importance of Buongiorno's two-phase model on the flow and thermal behaviour of A l 2 O 3 -water nanofluid. For this model, we investigate how changes in certain system parameters, such as the matrix porosity affect the flow, skin friction, the heat and mass transfer coefficients. The spectral quasilinearization method is used to solve the transport equations. The results show that an improvement in matrix porosity reduces the skin friction, the heat and mass transfer rates.